TREK channels in Mechanotransduction: a Focus on the Cardiovascular System - Herrera-Pérez, Salvador; Lamas, José Antonio (Frontiers in Cardiovascular Medicine, 2023)
Mechano-electric feedback is one of the most important subsystems operating in the cardiovascular system, but the underlying molecular mechanism remains rather unknown. Several proteins have been proposed to explain the molecular mechanism of mechano-transduction. Transient receptor potential (TRP) and Piezo channels appear to be the most important candidates to constitute the molecular mechanism behind of the inward current in response to a mechanical stimulus. However, the inhibitory/regulatory processes involving potassium channels that operate on the cardiac system are less well known. TWIK-Related potassium (TREK) channels have emerged as strong candidates due to their capacity for the regulation of the flow of potassium in response to mechanical stimuli. Current data strongly suggest that TREK channels play a role as mechano-transducers in different components of the cardiovascular system, not only at central (heart) but also at peripheral (vascular) level. In this context, this review summarizes and highlights the main existing evidence connecting this important subfamily of potassium channels with the cardiac mechano-transduction process, discussing molecular and biophysical aspects of such a connection.